Analysis of the Effect of Service Quality on Savings Customer Satisfaction at PT. BPRS Almadinah Tasikmalaya Perseroda - Maya Muharomah; Ganjar Santika; Muhammad Kaharudin Yasin (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study is to determine the effect of service quality on savings customer satisfaction at PT BPRS Almadinah Tasikmalaya Perseroda. This study used a quantitative descriptive research approach using raw data and data using simple linear regression. The results of this study show that service quality has a significant positive effect on customer satisfaction. The results of the t test show that the quality of service has a major positive effect on customer satisfaction, and the results of the t test are 7661 t table 1661. Therefore H0 is rejected and Ha is accepted because the independent variable affects the dependent variable with significance values of 0.000 0.05